Features of Javanese Woman in Hamka’s Merantau ke Deli - Pardi Pardi; Safitri Hariani (Proceedings of AICS - Social Sciences, 2017)
This study aims to find the features of Javanese woman through the novel Merantau Ke Deliby Hamka, with three points of discussion: hard-work, patience, and modesty. Hamka, through the novel tells about the cultural clash experienced by the protagonist, Leman. Staying for a living in Deli, North Sumatra, he marries Poniem, a strong, patient, modest, and hardworking Javanese woman. It is a prohibition in Minangkabau custom to marry a woman outside the clan. He should be back to Minangkabau one day and subject to the local custom and marries a woman from his clan to keep his status. As Leman’s first wife, she accepts his husband’s decision to marry Mariatun, as a second wife. This study is concerned with the features of Javanese woman having distinctive qualities of attitude and supported by Balance Theory of Attitude (Heider, 1958). The theory is basically concerned with the consistency in the judgment of people and or issues that are linked by some form of relationship. The sub-concepts of attitude are hard-work, meaning to give someone more time on particular work to get more practice and experience; patience, one of the exemplary characteristics of a religious man, along with sincerity, swiftness in understanding and tenderness and modesty, denoting a moderate self-view, seeing oneself as intermediate, rather than as very positive or very negative, on key personal attributes such as personality traits, abilities and skills, physical appearance, and social behaviour.The results show that the features are found in the novel.  Keywords:hard-work, patience, modesty, attitude.